PERBANKAN SYARIAH DI INDONESIA: - Euis Amalia (Sekretariat Badan Litbang dan Diklat Kementerian Agama RI, 2017)
This article discusses the development of Islamic banking in Indonesia, its contribution to and role in the constellation of national economy, particularly in empowerment of medium, small and micro enterprise (UMKM) which constitutes the pillar of national economy. This article also analyses a number of challenge faced by the Islamic banking institutions and attempts made by university as the centre for research, training human recourse to be capable and comprehend Islamic economy and to professionally develop Islamic financial industries, educating and advocating society for the strengthening of the regulation implementation. This is needed in order that the acceleration and development of Islamic banking in Indonesia could be realized in short time.